Medical Education and Human Cloning Challenges - alireza yousefy; azam alavi; narges sadeghi (مجله ایرانی آموزش در علوم پزشکی, 2012)
Introduction: Cloning technology has been strengthened a long human desire for eternal life. The possibility of human cloning is the new challenges in medical education and medical ethics. The present study discussed the different perspectives in this field. Methods: This study is a review article. Related books and some database such as SID, Irandoc, Elsevier, PubMed, Magiran were searched using keywords including human cloning, therapeutic cloning, reproductive cloning, ethics and medical education. The retrieved documents were reviewed. Results: Application of this technique for human being is condemned and opponents believed that this technique impairs human dignity and takes him down to the level of worthless merchandise. Different perspectives show that opponents consider fear of human dignity failure and its consequences as the most important points. Conclusion: It seems that cloning technologies are ahead of the law. Given the well-developed laws in Iran, Iran University of Medical Science can initiate this new science and technology in regional level